Monitoring stratification of anode biofilms in bioelectrochemical laminar flow reactors using flow cytometry - Yuting Guo; Luis F.M. Rosa; Susann Müller; Falk Harnisch (Environmental Science and Ecotechnology, 2020)
A laminar flow bioelectrochemical systems (BES) was designed and benchmarked using microbial anodes dominated with Geobacter spp. The reactor architecture was based on modeled flow fields, the resulting structure was 3D printed and used for BES manufacturing. Stratification of the substrate availability within the reactor channels led to heterogeneous biomass distribution, with the maximum biomass found mainly in the initial/middle channels. The anode performance was assessed for different hydraulic retention times while coulombic efficiencies of up to 100% (including also hydrogen recycling from the cathode) and current densities of up to 75 μA cm−2 at an anode surface to volume ratio of 1770 cm2 L−1 after 35 days were achieved. This low current density can be clearly attributed to the heterogeneous distributions of biomass and the stratification of the microbial community structure. Further, it was shown that time and space resolved analysis of the reactor microbiomes per channel is feasible using flow cytometry.